Facile synthesis of Cu doped cobalt hydroxide (Cu–Co(OH)2) nano-sheets for efficient electrocatalytic oxygen evolution. Issue 43 (25th October 2017) - Chen, Lisong; Zhang, Huilin; Chen, Li; Wei, Xinfa; Shi, Jianlin; He, Mingyuan
Abstract : Cu doped cobalt hydroxide with a uniform ultrathin structure was synthesized by a facile and green strategy. The synthesized samples show excellent oxygen evolution activity and stability. The possible reaction mechanisms for these samples have been proposed. Abstract : We report herein the facile synthesis of cobalt hydroxide nano-sheets with a uniform ultrathin structure under mild conditions. By doping heteroatoms such as Cu, the nanosheets' morphology and dimension can be well-tuned. The prepared heteroatom-doped cobalt hydroxide nano-sheets exhibit excellent catalytic activity and durability toward the oxygen evolution reaction (OER). In particular, Cu-doped cobalt hydroxide (Cu–Co(OH)2 ) shows an electrocatalytic current density of 10 mA cm −2 and a mass activity of 46 A g −1 at the overpotential of 300 mV, and a Tafel slope of 47 mV dec −1, which are markedly higher than those of the state-of-the-art IrO2 . Importantly, X-ray photoelectron spectroscopy (XPS) suggests the modulated electronic structure by the heteroatom doping, which implies that Co ions are more positively charged than the normal 2+ and is thus in favor of the OER performance. This work presents a green and facile strategy for the synthesis of heteroatom in situ doped ultrathin hydroxides which show excellent performance for the OER. A possible OER mechanism of this heteroatom doped Co(OH)2 material has also been proposed.